CONSIDERATIONS ON THE ISSUE OF DEFINING THE TERM "FIGHTING CRIME" - Kurbonov Doniyor Davlat o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
Crime is a social disease that poisons the society, for many years, people have tried to develop a medicine that will cure humanity and protect a person, his rights and freedoms from all kinds of crimes, but no single mechanism has been created that can fight crime.